Interdecadal Change of the Winter-Spring Tropospheric Temperature Over Asia and its Impact on the South China Sea Summer Monsoon Onset - You, Junli; Jian, Maoqiu; Gao, Si; Cai, Jingjiu (Frontiers in Earth Science, 2021)
The interdecadal change of the winter-spring tropospheric temperature over Asia and its impact on the South China Sea summer monsoon (SCSSM) onset are investigated in this study. The SCSSM onset experiences a significant advance around the mid-1990s, which is attributed to the positive interdecadal anomaly of meridional temperature gradient in the mid-upper troposphere in May over the South China Sea monsoon region. This positive interdecadal anomaly can be traced back to the previous winter and spring, mainly associated with the mid-upper tropospheric warming in the East Asian subtropics. During the anomalous seasonal evolution of the East Asian subtropical mid-upper tropospheric temperature, advection of the warm temperature anomaly by climatological mean wind overtakes the effects of anomalous adiabatic cooling and diabatic cooling, leading to a net interdecadal seasonal warming in winter. In spring, the adiabatic heating caused by the anomalous subsidence flow cannot offset the effects of anomalous cold advection and diabatic cooling, resulting in a net interdecadal seasonal cooling. However, the interdecadal seasonal cooling in spring is not strong enough to offset the interdecadal seasonal warming in winter, preserving an interdecadal mid-upper tropospheric warming over the subtropical East Asia in late spring. This interdecadal warming provides a favorable condition for the interdecadal advance of the SCSSM onset. Both observational analyses and numerical experiments suggest that the interdecadal change of atmospheric thermodynamic processes is related to the interdecadal warming in the tropical western Pacific. The enhanced convection and condensation heating over the regions from the South China Sea to the Philippines, forced by the tropical western Pacific warming, stimulates an anomalous anticyclone in the upper troposphere and warming in the whole troposphere over the subtropical East Asia.